2013
DOI: 10.3109/03009742.2013.776104
|View full text |Cite
|
Sign up to set email alerts
|

Repair of erosions in patients with rheumatoid arthritis treated with etanercept: magnetic resonance imaging findings after 1 year of follow-up

Abstract: Etanercept combined with DMARDs stopped the progression of erosions, as measured by the RAMRIS, in 82.8% of our RA patients and occasional repair of bone erosions occurred after 1 year of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…The OMERACT Subcommittee on Repair states that although SDC values are too large to be useful for determining repair at an individual patient level, using the SDC is currently appropriate . Previous reports revealed that a very small number of RA patients show negative changes in MRI erosion scores that exceed the SDC during therapy with biologic agents, that is, only 3.4% of patients treated with etanercept and 6% of patients treated with adalimumab therapy . On the other hand, we found that over 10% of patients showed definite regression of the MRI erosion scores.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…The OMERACT Subcommittee on Repair states that although SDC values are too large to be useful for determining repair at an individual patient level, using the SDC is currently appropriate . Previous reports revealed that a very small number of RA patients show negative changes in MRI erosion scores that exceed the SDC during therapy with biologic agents, that is, only 3.4% of patients treated with etanercept and 6% of patients treated with adalimumab therapy . On the other hand, we found that over 10% of patients showed definite regression of the MRI erosion scores.…”
Section: Discussioncontrasting
confidence: 40%
“…Second, there was no control group. Third, the observation period was limited in duration for ideal assessment of erosion repair …”
Section: Discussionmentioning
confidence: 99%
“…Radiographically, erosion healing in RA patients treated with disease-modifying anti-rheumatic drugs (especially biologic agents) occurs in 7-11% of patients [72,73] and in approximately 4% of affected joints [74]. MRI studies demonstrate decreased size in a minority (17%) of erosions in RA patients managed with these agents at 1 year, with partial repopulation of the affected bone by marrow fat at 6 years [75,76]. However, in individual patients, if there is any partial erosion repair, progression and development of new erosions typically occur simultaneously [73].…”
Section: Erosionsmentioning
confidence: 99%
“…for the treatment of rheumatoid, juvenile rheumatoid and psoriatic arthritis [9,10]. Recent clinical data have indicated that Etanercept also has beneficial effects on preventing bone erosions in rheumatoid arthritis and psoriasis [11,12]. Given the emerging evidence that TNF-α plays a similar and central pathogenetic role in prosthetic loosening and rheumatoid arthritis, we proposed that Etanercept has the ability to inhibit wear debris induced osteolysis.…”
Section: Introductionmentioning
confidence: 99%